A Solution for the Shortage of Detection Dogs: A Detector Dog Center of Excellence and a Cooperative Breeding Program - Leighton, Eldin A.; Hare, Elizabeth; Thomas, Scott; Waggoner, L. Paul; Otto, Cynthia M. (Frontiers in Veterinary Science, 2018)
Currently, demand for US-bred and born detector dogs exceeds available supply, while reliance on foreign-bred sources introduces many unnecessary and unwanted risks. With proper management of a domestic supply line, U.S. breeders can improve both health and behavior by applying scientific principles to breeding and raising of detector dogs. A cooperative national detector dog breeding and development program will mitigate the current shortage of domestic-bred dogs that meet the health and behavior standards required by government, military, and law enforcement agencies. To coordinate such a cooperative, we propose a Detector Dog Center of Excellence (DDCoE) led by representatives of academic canine science programs guided by an advisory board of stakeholders. As a non-governmental organization, the DDCoE will oversee selective breeding of dogs owned by breeders, purchase the resulting puppies, and its members will supervise puppy raising until dogs are of a suitable age to be purchased by government agencies or other working dog organizations. The DDCoe will serve as an approved vendor to facilitate the procurement process. Breeding decisions will be based on proven quantitative genetic methods implemented by a specialized database. A national working dog semen bank will ensure conservation of diverse genetic material and enhance selection response by providing numerous potential sires. As a data collection and genetic evaluation center, the DDCoE will lead research to define quantitative traits involved in odor detection, to understand how these traits develop, and methods to optimize training of dogs endowed with enhanced odor detection ability.